Existence and Uniqueness of Positive Solutions for a Coupled System of Fractional Differential Equations - Hanying Feng; Xiaofeng Zhang (Discrete Dynamics in Nature and Society)
In this article, we investigate a boundary value problem for a coupled differential system of fractional order that the nonlinear term depends on the unknown functions as well as their lower order fractional derivatives. Firstly, we give Green’s functions and prove their properties; secondly, the existence and uniqueness of positive solutions are obtained by using some fixed point theorems. In addition, two examples are presented to demonstrate the application of our main results.